PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR( OCB) DI PT. ARGAMUKTI PRATAMA SEMARANG - Arif Hidayat Hidayat; Ratna Kusumawati Kusumawati (AKSES: Jurnal Ekonomi dan Bisnis, 2014)
This study aimed to determine the influence of organizational commitment and job satisfactionon Organizational Citizenship Behavior (OCB) PT. Argamukti Pratama either partially or simultaneously.The samplesin this study wereas many as 134 respondents. The data was collected using aquestionnaire. Each respondent was asked his opinion by giving answers of the claims filed. Data was collected usinga closedquestion. After that testedthe validity and reabilityusing SPSS or Statistical Program for Social Science. Data Analysis Techniques processedusing SPSS or Statistical Program for Social Science. Results of this study indicate that organizational commitment have significant positive effecton Organizational Citizenship Behavior (OCB), job satisfaction have significant positive effecton Organizational Citizenship Behavior (OCB) and organizational commitment and job satisfaction has significant positive effect simultaneously. Keywords :      Organizational Commitment, Job Satisfaction, Organizational Citizenship Behavior(OCB).